Transaksi Cryptocurrency Dalam Perspektif Hukum Islam - Ilham, Muhammad; Dwi Pamungkas, Erna (Yayasan Dar Arrisyah Indonesia, 2024)
Transactions and investments using cryptocurrency in their application based on Islamic law are still debated. Cryptocurrency is a transaction tool that can be used easily and safely, but remember that cryptocurrency can be haraam because it is something whose physical condition is uncertain or unknown. It can be concluded that cryptocurrency is a digital currency where transactions can be carried out online. Unlike printed paper currency, cryptocurrencies are designed by solving mathematical problems based on cryptography. This currency was formed based on Cryptographic technology so that it cannot be easily duplicated or transferred to other parties who are not the owner and do not have access to this currency. In determining or establishing cryptocurrency laws, Islam has its own methods and reference sources, first from the Koran and second from al-Hadith, third from Qiyas and fourth from Sadd-adzariah. The pros and cons that occur in society regarding cryptocurrency have not yet reached a clear point. In Indonesia itself, the government has not taken a definite stance on the existence of cryptocurrency. Even cryptocurrency is not a legal means of payment in the country. This is in accordance with the regulations of Law No. 7, Article 1 Paragraph 1, 2011, that the means of payment accepted in Indonesia only use the Rupiah currency. From the perspective of Islamic law, cryptocurrency may contain elements of gharar and maysir, because its use is for speculation and its physical form cannot be seen.